The Use of Sea Sand as a Substitute for Fine Aggregate in High-Strength Concrete - Nurul Hidayati; Hariyadi Hariyadi; Ahmad Zarkasi; Muhammad Holikul Bahari Kusuma (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2026)
Concrete is a common construction material whose quality depends on parameters such as compressive strength and split tensile strength. To reduce the environmental impact of river sand use, this study evaluates the use of sea sand as a partial replacement for fine Aggregate. Although sea sand contains salt, special treatment can reduce its salt content and is expected to improve the quality of high-grade concrete. The objectives of this study were to assess the impact of sea sand on the mechanical strength of concrete and to determine the optimum percentage of sea sand in high-quality concrete mixtures. This study used compressive strength, split tensile strength, and shear strength testing methods with variations in sea sand content in concrete mixtures of 0%, 25%, 50%, and 100%. The tests were conducted using a Compression Testing Machine (CTM). The results showed that using sea sand reduced the mechanical strength of concrete. Compressive strength decreased from 43.09 MPa to 29.91 MPa, splitting tensile strength decreased from 4.23 MPa to 1.21 MPa, and shear strength decreased from 10.23 MPa to 5.97 MPa with an increase in the percentage of sea sand. Therefore, it can be concluded that although sea sand can be used, its use in large quantities reduces the mechanical strength of concrete. The optimum percentage must be adjusted to balance sustainability and structural strength.